The influence of school facilities and the work environment on teachers performance - Eka Purnama Sari; Syarwani Ahmad; Destiniar Destiniar (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aims to determine the effect of infrastructure and work environment together on the performance of public elementary school teachers in Gugus 3, Lengkiti District. In this study, using quantitative research methods and research design in the form of influence studies, namely to determine the effect of the three variables, namely the independent variable or free school infrastructure (X1), work environment (X2) and the dependent or dependent variable Teacher Performance (Y). The results of the study can be concluded as follows: 1) There is a significant influence between school infrastructure on the performance of teachers at SD Negeri Gugus 3, Lengkiti District, 2) There is a significant influence between the work environment on the performance of teachers at SD Negeri Gugus 3, Lengkiti District, 3) There is an influence between the school infrastructure and the environment together on the performance of teachers at SD Negeri Gugus 3, Lengkiti District.